-8(3x+4)+6x=4(x-8)+4x

Simple and best practice solution for -8(3x+4)+6x=4(x-8)+4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8(3x+4)+6x=4(x-8)+4x equation:


Simplifying
-8(3x + 4) + 6x = 4(x + -8) + 4x

Reorder the terms:
-8(4 + 3x) + 6x = 4(x + -8) + 4x
(4 * -8 + 3x * -8) + 6x = 4(x + -8) + 4x
(-32 + -24x) + 6x = 4(x + -8) + 4x

Combine like terms: -24x + 6x = -18x
-32 + -18x = 4(x + -8) + 4x

Reorder the terms:
-32 + -18x = 4(-8 + x) + 4x
-32 + -18x = (-8 * 4 + x * 4) + 4x
-32 + -18x = (-32 + 4x) + 4x

Combine like terms: 4x + 4x = 8x
-32 + -18x = -32 + 8x

Add '32' to each side of the equation.
-32 + 32 + -18x = -32 + 32 + 8x

Combine like terms: -32 + 32 = 0
0 + -18x = -32 + 32 + 8x
-18x = -32 + 32 + 8x

Combine like terms: -32 + 32 = 0
-18x = 0 + 8x
-18x = 8x

Solving
-18x = 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
-18x + -8x = 8x + -8x

Combine like terms: -18x + -8x = -26x
-26x = 8x + -8x

Combine like terms: 8x + -8x = 0
-26x = 0

Divide each side by '-26'.
x = 0

Simplifying
x = 0

See similar equations:

| 0=-16t^2+10t+50 | | -36+20= | | -6-24y=8x | | -6-24=8x | | 2g+g-7=1+3g | | 4x+6x+2+8=5x+5+4x | | -(6y+1)=-4(-10-4y) | | 2(12-8x)=2+14t | | 3y=-3x-1 | | 0.2k-4.21-0.8k=2(-k+0.1) | | 37=-3x-1 | | 0.1x+5=.15+3 | | 22m=4.4 | | 10+15+y=16.45 | | 6y+3x-4=0 | | -8x+y=4 | | 3/4-y=1/2(4y+7) | | 5-(-20/10) | | 4x^7*-6x^3= | | 4(4-2x)=-24 | | 11.2+4(2.1+9)=0.8 | | -2(-8)+4y=-8 | | 11.2+4(2.1+9)= | | d^2-21=0 | | -4x-2=10 | | 2x+13x+6=0 | | -5=0.25(4+20r) | | 7x/9*2/7=8x/63 | | x+7y=31 | | x^2-1/4x | | 8x+5=-107 | | 6+2x+7x=15 |

Equations solver categories